Navigating paths to food security in East Africa: strengthening rural development amid climate shocks, political instability, and rising food prices - Abdi, Abdikafi Hassan; Mohamed, Abdisalan Aden; Sheikh, Sudi Nur (Frontiers in Political Science, 2025)
As the most food-insecure region in Africa, East Africa faces persistent challenges in ensuring adequate food supply, as climatic fluctuations, political instability, and economic hardships continue to undermine its ability to meet the dietary needs of its growing population. While previous research has predominantly examined climate change and political instability as primary drivers of food insecurity, the influence of rural development on food security outcomes remains insufficiently explored. Hence, this study investigates the relationship between rural development and food security while incorporating climatic and socio-economic factors using panel data from 12 countries between 2001 and 2020. Employing heterogeneous panel cointegration techniques, the findings derived from PCSE and FGLS estimators reveal that rainfall substantially improves food availability and utilization while diminishing food accessibility and stability. In contrast, higher temperatures negatively affect all four dimensions of food security. Moreover, population growth exerts a significant negative influence on food availability and stability, while food imports enhance food availability but simultaneously reduce accessibility and utilization. Furthermore, political stability is crucial in strengthening food availability and stability, whereas rural development significantly boosts food availability, accessibility, and utilization. Nevertheless, the Dumitrescu–Hurlin panel tests indicate bidirectional predictive linkages between population growth and food security, and a unidirectional linkage from temperature to food security. These findings propose targeted recommendations for East African authorities to strengthen food security policies and resilience.